Eﬀect of breathing exercises with biofeedback on blood pressure in pre-hypertensive women: a randomised controlled trial - Botla, Afaf M.; Ebrahim, Reham S.; Elkosery, Soheir M.; Darwesh, Ahmed M.; Mohamed, Dina M.A. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. Pre-hypertensive women are signiﬁcantly more likely to develop hypertension or serious cardiovascular disease (CV). Autonomic nervous system abnormalities, such as sympathetic overactivity and parasympathetic withdrawal, are most likely the earliest functional changes in hypertension. The objective of this study was to determine the eﬀect of breathing exer-cises with biofeedback on blood pressure (BP), heart rate variability (HRV), respiratory rate (RR), and skin galvanic response (SGR).Methods. Thirty middle-aged women with pre-hypertension (120/80–139/89 mm Hg) were recruited from Ain Shams University. They were divided randomly into two equal groups, with ages ranging from 30 to 40: study group (group A) who performed slow abdominal breathing (six cycles/minute) combined with frontal electromyography (EMG) biofeedback training (3 days per week for 10 sessions) and a control group (group B) who performed slow abdominal breathing (six cycles/minute, 3 days per week for 10 sessions). All subjects were assessed by measuring systolic blood pressure (SBP), diastolic blood pressure (DBP), HRV, RR, and SGR levels before and after the intervention.Results. SBP, DBP, RR, and SGR mean values showed a statistically signiﬁcant decline; however, group A’s HRV post-treatment increased signiﬁcantly compared to pre-treatment (p = 0.001). In group B, there was no signiﬁcant diﬀerence in DBP or SGR; however, there was a substantial drop in SBP and HRV (p = 0.001) and a signiﬁcant rise in RR (p = 0.001). Following therapy, there was a signiﬁcant diﬀerence between the two groups in terms of DBP, HRV, RR, and SGR (p = 0.001), favouring group A.Conclusions. As a result, it is possible to infer that breathing exercises combined with biofeedback were beneﬁcial in lowering BP in middle-aged pre-hypertensive women.
Keywords: pre-hypertensive women; blood pressure; breathing exercises; biofeedback